SEARCHING COMMON EUROPEAN STANDARDS REGARDING BLASPHEMY? ANALYSIS OF ITALIAN, IRISH, AUSTRIAN REGULATION FROM THE LIGHT OF THE ECHR - Hanna Monika Wiczanowska (Torun International Studies, 2019)
The purpose of the presented article is to resolve the issue of the existence of the common European standard regarding the blasphemous speeches and examine its efficiency for possible mechanisms of resolving the collussion between freedom of expression and freedom of religion. The presented analysis will be commenced with reference to the judicial practice of the European Court of Human Rights regarding the tension between freedom of expression and freedom of religion with addition to blasphemy. Through the prism of such analysis the author formulates hypothesis of the wide diversity between the States of the Council of Europe towards granting priority for one of the aforesaid freedoms in case of blasphemy. Secondary question refers to the influence of such diversity for the efficiency of protection of both: freedom of expression and freedom of religion. Subsequently the author will analyse the domestic regulations of Italy, Ireland and Austria to illustrate the occurring differences as well as search for optimal model of protection. The author will also refer to the statement of selected representatives of human rights doctrine. The conclusion part will focus on formulating recommendations for amplifying the efficiency of the common European standard regarding the presented issue. The author will rely mainly on legal dogmatic methodology with reference to the literal resonance of the legal regulations as well as judicial practice of the European Court of Human Rights as well as comparative analysis to unveil similarities and differences within presented States legal systems.